Every last lie [compact disc, unabridged] - Kubica, Mary (Harlequin Audio, 2017)
New York Times best selling author of The Good Girl, Mary Kubica is back with another exhilarating thriller as a widow's pursuit of the truth leads her to the darkest corners of the psyche.